Efisiensi Penggunaan Media Kotak Huruf Dalam Meningkatkan Kemampuan Membaca Permulaan pada Anak Tuna Grahita di SLB Negeri Manekat Niki-Niki - Dejukamin, Alberto; Selan, Ot Bil Wilson; Wangge, Vinsensius; Talan, Rudobertus (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve early reading skills in children with mild mental retardation at SLB Negeri Manekat Niki-Niki. Children with special needs, especially mental retardation, often face obstacles in concentration and understanding of material, especially in basic reading skills. Initial observations showed that mentally retarded students at the school had significant variations in early reading skills, with some of them still requiring intensive guidance. To overcome this problem, the researcher used letterbox media as a learning aid. The research method used was Classroom Action Research (CAR) with two cycles. Each cycle consists of four meetings, including the delivery of material and post-action tests. The results in cycle I showed weaknesses in recognizing vowels, consonants, and syllables without teacher assistance. However, after improvements were made in the learning process in cycle II, there was a significant increase in students' initial reading ability. This increase was due to improvements in the teaching and learning process that made students more enthusiastic. Based on these findings, it is concluded that the use of letter box media is effective in improving the initial reading ability of children with mild mental retardation.